Importance of surface methods in human and automatic text summarization - Mikelić Preradović, Nives (Array, 2014)
Both human and automatic summaries enable a concise display of the most important information from the original text. Summaries written by the author of the document, expert in the field, professional summarizer or generated by the automatic summarization system use the same shallow feature of the text (such as word frequency or location) to create a high- quality summary. In this paper, we describe these features and compare summary written by human with a summary created by automatic text summarization systems: Microsoft Word, SweSum, SHVOONG and Online Brevity Document Summarizer. Research results show that although all these automatic summarizers rely heavily and only on the shallow features of the text, they all generate informative extracts satisfying quality expectations of the human users.